Respuesta :

14 = -(p-8)

Step 1 : Distribute the negative sign. This is equivalent to multiplying each term in the parenthesis by -1.
14 = -p+8

Step 2: Subtract 8 from each side to isolate the -p.
14 - 8 = -p +8 - 8
6 = -p

Step 3: Multiply everything by -1 to get what p is equivalent to.
6 * -1 = -p * -1
-6 = p
Which can be rewritten as
p = -6
Setor9
Follow the step
14=-(p-8)
14=-1(p-8). DISTRIBUTE -1
14=-p+8. SUBTRACT 8 FROM BOTH SIDES
-8 -8
6=-p DIVIDE -1 ON BOTH SIDES
6/-1=-p/-1
-6=p
So P is -6


ACCESS MORE